Strategic trade policy as response to climate change? - Andreas Freytag; Leo Wangler (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
This paper discusses the political economy of the climate change debate. The objective is to come to a better understanding of why at international levels (e. g. the G8 summit in Heiligendamm) climate change was one of the main topics at the agenda, despite the fact that climate change cannot be solved by only eight participating countries, even if these eight countries are considered as the biggest in the world. The problem of climate change is a supranational one and needs supranational cooperation. Using a strategic trade policy framework, the paper theoretically and from a positive perspective explains why countries like Germany are more engaged in policies related to climate change than other industrial countries, which also have signed the Kyoto Protocol.
Keywords: 330; Klimaschutz; Internationale Zusammenarbeit; Strategische Handelspolitik; Public Choice; Theorie; Industriestaaten